Unhoming Pigeons: The Postal Principle in Lynn Hershman Leeson and Hussein Chalayan. - Turner, Lynn (Derrida Today, 2012)
In this article I bring together Jacques Derrida and Luce Irigaray's engagements with Sigmund Freud's vexed attempt to step beyond the pleasure principle. Derrida's speculations on the name, the house and the practice of Freud find him inadvertently rewriting the conditions of the autobiographical as that which erases as much as inscribes, while Irigaray requires a sexually different modelling of what we call language if the experience of the girl is to be addressed. Yet Irigaray uncannily repeats the teleological gesture of laying claim to a legacy, diagnosed in Freud by Derrida, even as this legacy is newly imagined as that of the feminine to which Freud remained blind. I then interweave these revised stakes of the fort-da game as they are expressed in two experimental films; Lynn Hershman Leeson's feature Conceiving Ada (USA, 1997) and Hussein Chalayan's short Absent Presence (UK/Turkey, 2005). One self-consciously concerns the recovery of 'lost' women from history ( da!), the other investigates the treatment of the foreigner staged with an all-female cast (in which the instability of foreign objects can secure no fortification for the scientific subject). The films differently engage fantasies concerning genetics, and differently engage the projection of a legacy as teleological ambition. Privileging Derrida's transformation of the pleasure into the postal principle as that which invokes 'Tele-without telos', I ask after the transmissibility of this ambition.